Development of monitor system for parallel-type superconducting level sensor for liquid hydrogen. (September 2019) - Tanaka, Naoki; Kajikawa, Kazuhiro; Oguro, Hidetoshi; Sugino, Makoto; Nakanishi, Tsutomu; Aoki, Itsuo
Abstract: We develop a monitor system to control a parallel-type superconducting (SC) level sensor and to indicate the level of liquid hydrogen in a container. The parallel-type level sensor is composed of an MgB2 wire and non-SC wire, which are vertically located in parallel and electrically connected in series. We assemble the monitor unit using a power supply, central processing unit (CPU), analog-to-digital (AD)/digital-to-analog (DA) converter, touch panel, voltage dividers and isolators. The terminal voltages of the MgB2 wire and non-SC wire with a constant current produced by the power supply are stored in the memory of CPU through the isolators, voltage dividers and AD converter. The liquid level is calculated in the CPU according to a pre-written program code. The obtained result is displayed on the touch panel and also output externally via the DA converter and isolator. Furthermore, the normal operation of the developed monitor system is validated using dummy voltages from an oscillator.